A CRITICAL ASSESSMENT OF MAPS AND THE INTERNET - Peterson, Michael P. (Revista Brasileira de Cartografia, 2009)
The promise of the Internet for cartography has faded into stark realities of commercialism, connectivity problems and confusion about what represents quality in Internet mapping. Accessing the Internet is still problematic and a great digital divide separates the developed from the developing world. Interaction with the online map, the single greatest advantage of maps and the new medium, has been either poorly implemented or not incorporated at all. The commercial aspect of the Internet has been turned upside down. We pay to access the Internet, not for its content. As a result, there is little competition to improve the quality of online maps, other than for bragging rights, and little incentive to create quality content. On top of this, in many parts of the World, access to the Internet by computer is expensive or inconvenient or people prefer to use the Internet through their mobile phone. Almost all new users to the Internet are connecting through mobile devices and a small screen that is hardly suitable for the display of maps. While a de-centralized system like the Internet is impossible to fix in traditional ways, solutions must be found for making the medium more accessible and useful for maps. National and international organizations can play a key role in providing examples of what is possible with maps and the Internet. Low-cost, easy-to-use tools also need to be made available so that online cartographers can create quality content.